2011
DOI: 10.5402/2011/954626
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ammonia Toxicity in Landfill Leachates

Abstract: Toxicity identification evaluation (TIE) phase I manipulations and toxicity test with D. magna were conducted on leachates from an industrial waste landfill site in Japan. Physicochemical analysis detected heavy metals at concentrations insufficient to account for the observed acute toxicity. The graduated pH and aeration manipulations identified the prominent toxicity of ammonia. Based on joint toxicity with additive effects of unionized ammonia and ammonium ions, the unionized ammonia toxicity (LC50,NH3(aq))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Ammonia is mostly contributed by the decomposition of protein, and a level of 500 to 2000 mg/L NH 3 -N is common (Kjeldsen et al 2002). Osada et al (2011) found that ammonia contributes 58.7 % to the total toxicity of landfill leachate. …”
Section: Resultsmentioning
confidence: 99%
“…Ammonia is mostly contributed by the decomposition of protein, and a level of 500 to 2000 mg/L NH 3 -N is common (Kjeldsen et al 2002). Osada et al (2011) found that ammonia contributes 58.7 % to the total toxicity of landfill leachate. …”
Section: Resultsmentioning
confidence: 99%
“…Concentrations at which ammoniacal-nitrogen (NH 4 + -N-NH 3 ) toxicity becomes inhibitory varies greatly with individual algal species and culture conditions [5]. Osada et al [24] reviewed the specific toxicants masked by NH 3 toxicity. NH 3 toxicity contributed to 58.7% (by volume) and other toxicants to 41.3% of the total toxicity of the LFL.…”
Section: Microalgal Growth and Nitrogen (Nh 4 + -N And No 3 -N) Removmentioning
confidence: 99%
“…From bioassay studies using different test organisms, LFL toxicity have been monitored, and it can be inferred that of all the toxic compounds that remain in stabilized LFL, Ammoniacal nitrogen (NH 4 + -N-NH 3 ) has been identified as one of the major toxicants to living organisms [20,23,24]. Organic compounds in dumped waste produce NH 3 -N due to hydrolysis and fermentation of the nitrogenous fractions of biodegradable substrates [23].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of ammonium toxicity most often include ammonium hyperaccumulation in tissues [12]- [14] and are coupled with 29 a disruption in cation homeostasis, leaf chlorosis, root growth inhibition, and reduced plant biomass. Ammonium sensitivity can also be observed in animals and humans [9].…”
Section: Introductionmentioning
confidence: 99%
“…Starting in the middle of the last century the "green revolution" was based on the excessive use of mineral Nfertilizers that lead to volatilization of ammonia (NH 3 , a greenhouse gas) and the deposition of ammonium ions (NH 4 + ) in soils [6]. Soil solutions derived from agricultural areas may reach ammonium levels as high as 40 mM [7], while forest-floor soil solutions and landfill leachates contain an order of magnitude less [8], [9]. Although ammonia is the final form of inorganic nitrogen prior to the biosynthesis of organic nitrogen compounds [10], paradoxically at higher concentrations it is phytotoxic [11] that may result in limitations of the yield.…”
Section: Introductionmentioning
confidence: 99%